2017
DOI: 10.1371/journal.pone.0174523
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inhibition of influenza A virus replication by RNA interference targeting the PB2 subunit via intratracheal delivery

Abstract: BackgroundInfluenza virus infection is a major threat to human health. Small interfering RNA (siRNA) is a promising approach for the prevention and treatment of viral infections. In this study, we constructed a series of DNA vector-based short hairpin RNAs (shRNAs) that target various genes of the influenza A virus using the polymerase III U6-RNA promoter to prevent influenza virus infection in vitro and in a mouse model.ResultsThree sets of DNA vector-based shRNA, two targeting genes encoding the polymerase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It was observed that shRNAs cloned in pSilencer2.1-U6 puro plasmid vector had a prophylactic effect on the mice infected with A/WSN/33 (H1N1) when delivered as shRNA-jetPEI complex through intra-tracheal route. However, these complexes could not show any therapeutic efficacy [137]. Another study was done on siRNA designed against gene encoding phosphoprotein of RSV.…”
Section: Methods Of Delivery and Challengesmentioning
confidence: 99%
“…It was observed that shRNAs cloned in pSilencer2.1-U6 puro plasmid vector had a prophylactic effect on the mice infected with A/WSN/33 (H1N1) when delivered as shRNA-jetPEI complex through intra-tracheal route. However, these complexes could not show any therapeutic efficacy [137]. Another study was done on siRNA designed against gene encoding phosphoprotein of RSV.…”
Section: Methods Of Delivery and Challengesmentioning
confidence: 99%
“…The group of silencers includes antisense oligonucleotides (ASO), ribozymes, DNAzymes, short interfering RNAs (siRNA), microRNAs (miRNAs), short hairpin RNA (shRNAs), or peptide nucleic acids (PNAs). The evidence for their effectiveness in vivo has been provided in many, including those performed in our group [87][88][89][90][91][92]. However, the use of synthetic nucleic acids is limited due to imperfect systems of their introduction into cells.…”
Section: Nanotechnology In Gene Silencing Strategiesmentioning
confidence: 99%
“…As all siRNAs are not equally potent, various rules have been suggested for the computational prediction, designing, and selection of potential siRNAs. Currently, the siRNA approach has been implemented to inhibit viral replication in cell culture against many viruses like HIV ( Liu et al, 2017 ), Flock house virus (FHV) ( Taning et al, 2018 ), Dengue virus ( Idrees and Ashfaq, 2013 ), Hepatitis C virus (HCV) ( Shahid et al, 2017 ), Influenza virus ( Huang et al, 2017 , Tsai et al, 2018 ), Hepatitis B virus (HBV) ( Wang et al, 2016 ), Human Papillomavirus (HPV) ( Zeng et al, 2017 ) and SARS coronavirus (SARS-CoV) ( Kumar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%